2000
DOI: 10.1128/aem.66.1.223-229.2000
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Sous Vide-Processed Products with Respect to Nonproteolytic Clostridium botulinum by Use of Challenge Studies and Predictive Microbiological Models

Abstract: Sixteen different types of sous vide-processed products were evaluated for safety with respect to nonproteolytic group II Clostridium botulinum by using challenge tests with low (2.0-log-CFU/kg) and high (5.3-log-CFU/ kg) inocula and two currently available predictive microbiological models, Food MicroModel (FMM) and Pathogen Modeling Program (PMP). After thermal processing, the products were stored at 4 and 8°C and examined for the presence of botulinal spores and neurotoxin on the sell-by date and 7 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…Considerable temperature abuse may be necessary before these strains in chilled foods will grow and produce enough toxin to cause outbreaks. Nevertheless, certain strains of group II C. botulinum have been reported to grow slowly and produce toxin at 3°C (5,7,29) and at 4 to 5°C within a time frame typical for storage of chilled foods (6,14,24). Therefore, minimally processed chilled foods should receive special attention with regard to C. botulinum.…”
Section: Discussionmentioning
confidence: 95%
“…Considerable temperature abuse may be necessary before these strains in chilled foods will grow and produce enough toxin to cause outbreaks. Nevertheless, certain strains of group II C. botulinum have been reported to grow slowly and produce toxin at 3°C (5,7,29) and at 4 to 5°C within a time frame typical for storage of chilled foods (6,14,24). Therefore, minimally processed chilled foods should receive special attention with regard to C. botulinum.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that the lack of growth within the time that the experiment was monitored was due to an extended lag phase. Hyytia-Trees et al (2000) demonstrated that the storage temperature of sous vide foods did not have a considerable effect -very little growth occurred during storage at 8°C, which was also inconsistent with FMM predictions. Different non-proteolytic strains of C. botulinum have varied growth patterns (Brown et al, 1991) and this should be considered when comparing growth data.…”
Section: Growth Of Clostridium Botulinummentioning
confidence: 60%
“…The risk of botulism was confirmed with a number of sous vide (cooked under vacuum) products challenged with this pathogen: carrot, chicken and cod (Brown & Gaze, 1990;Brown, Gaze, & Askell, 1991); spaghetti and meat sauce ; ground beef and pork cubes (Lindstrom et al, 2001); beef roast and rice-based dishes (Hyytia-Trees et al, 2000); soups, casseroles and curries (Rodgers, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…1991). The poor growth of this pathogen in sous‐vide meals was reported by Hyytia‐Trees et al . (2000) and Rodgers (2002); the low temperature (<5°C) and pH (<5.5) were adequate to control growth and toxin production.…”
Section: Challenge Studiesmentioning
confidence: 61%